2021
DOI: 10.1111/anu.13296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lipid levels on growth performance, hepatic health, lipid metabolism and intestinal microbiota on Trachinotus ovatus

Abstract: The shortage of fishmeal is the main restrictive factor for developing aquaculture, which impedes economic and social development in many countries, including China. Compare to protein, lipid was regarded as the cheaper energy resource, especially to carnivorous fish, which prefer lipid rather than carbohydrate (Council, 2011).Lipid is one of the primary nutrients in natural feed and an indispensable ingredient in high-efficiency compound feed. Previous studies showed that increasing dietary lipids enhanced gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Studies have shown that activation of pparα could promote fatty acid β-oxidation by promoting the expression of cpt1, which is the rate-limiting enzyme for fatty acid oxidation [57,58]. For small and medium turbot, expressions of pparα and cpt1 in the L171.2 group were significantly lower than that in other groups, similar to a previous study in Trachinotus ovatus, demonstrating that excessive lipid intake might reduce hepatic lipolysis by the pparα-cpt1 signal pathway [59]. Nevertheless, experimental diets had no significant effect on expressions of pparα and cpt1 in large turbot, which might be due to the greater tolerance to high lipids of the large turbot.…”
Section: Discussionsupporting
confidence: 86%
“…Studies have shown that activation of pparα could promote fatty acid β-oxidation by promoting the expression of cpt1, which is the rate-limiting enzyme for fatty acid oxidation [57,58]. For small and medium turbot, expressions of pparα and cpt1 in the L171.2 group were significantly lower than that in other groups, similar to a previous study in Trachinotus ovatus, demonstrating that excessive lipid intake might reduce hepatic lipolysis by the pparα-cpt1 signal pathway [59]. Nevertheless, experimental diets had no significant effect on expressions of pparα and cpt1 in large turbot, which might be due to the greater tolerance to high lipids of the large turbot.…”
Section: Discussionsupporting
confidence: 86%
“…In consideration of these results, the TLR signaling pathway may play a role in the potential effects of LPC supplementation on intestinal physiology. Meanwhile, as known, high-lipid diet-induced intestinal damage was associated with the disruption of the intestinal mucosal barrier in both humans and fish [ 15 , 45 ]. Previous studies in Nile tilapia ( Oreochromis niloticus ) and rice field eel ( Monopterus albus ) have demonstrated that high-lipid diets can stimulate the TLR/NF-κB signaling pathway to regulate the expression of inflammatory cytokines [ 11 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In modern aquaculture, in order to spare dietary protein, the use of high-lipid diets is becoming more and more popular. However, a variety of problems resulting from high-lipid diets have occurred, including damage of fish intestines [ 13 , 14 , 15 ]. Accumulating evidence indicates that intestinal inflammation induced by high levels of dietary lipid is associated with TLR-signal transduction in both mammals and fish [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatopancreas samples were homogenized and centrifuged according to the methods of Fang et al, 2021b). Briefly, hepatopancreas samples and phosphate buffer (1:10) were mixed and homogenized, and then centrifuged for 10 min (4 • C, 1,200 g), and the supernatants were collected.…”
Section: Detection Of Hepatopancreas and Hemolymph Antioxidant Parametersmentioning
confidence: 99%